ĐẶC ĐIỂM SINH HỌC CỦA CHỦNG Aspergillus terreus VNA 05 VÀ KHẢ NĂNG SINH TỔNG HỢP LOVASTATIN - Chu, Thanh Bình; Nguyễn, Thu Hoài (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
BIOLOGICAL CHARACTERISTICS OF THE STRAIN Aspergillus terreus VNA 05 AND THEIR LOVASTATIN BIOSYNTHESIS CAPABILITYThis paper presents some biological features and lovastatin biosynthesis capability of strain A. terreus VNA 05. It is found that the strain is capable of lovastatin biosynthesis and develops well in pH from 5 to 7.5 and at temperature 28oC - 30oC. The train consumes some commonly used carbon sources (glucose, saccharose, glycerol,mannose, lactose) and nitrogen sources (yeast extract, soybean powder, corn extracted water, peptone). A. terrus VNA 05 also yields enzyme activities hydrolyzing starch, casein, gelatin, xelluloza, which are favorable conditions for selecting nutrients during lovastatin fermentation.